ANALISIS PENGARUH REKOMENDASI THE FINANCIAL ACTION TASK FORCE (FATF) DALAM UPAYA PENANGANAN BETTING ACTIVITIES DAN MATCH- FIXING PADA PERTANDINGAN SEPAK BOLA DI SINGAPURA - Pradipta, Benediktus Agya; Putranti, Ika Riswanti (Journal of International Relations, 2018)
Money laundering through the football sector according to the FATF report can be present through several channels, one of which is betting activities that in practice has a close connection with match-fixing. The linkages between the two is carrying a complex and broad dimension. This is not separated from the role of Singaporean criminal organizations that involved in many cases throughout the world. In responding to this, Singapore took two crucial policies as a handling effort after previously not recognizing that its country was the base of the perpetrators of betting activities and match-fixing. This research aims to describe and analyze the influence of the FATF Recommendation which is understood as the AML / CFT regime towards Singapore in handling related cases. The conceptual framework used is the concept of an international regime from Krasner (1983) and Barkin (2006) by using a rationalist approach that has a focus of discussion on the regulative effects of a regime in influencing a country's attitude or behavior. This study shows that changes in attitude through a policy adopted by Singapore in handling betting activities and match-fixing as an influence of the process of "accepting" and "complying" with FATF recommendations.